In vivo regulation of erythropoiesis by chemically inducible dimerization of the erythropoietin receptor intracellular domain. - Norio Suzuki; Harumi Y Mukai; Masayuki Yamamoto (PLoS ONE, 2015)
Erythropoietin (Epo) and its receptor (EpoR) are required for the regulation of erythropoiesis. Epo binds to the EpoR homodimer on the surface of erythroid progenitors and erythroblasts, and positions the intracellular domains of the homodimer to be in close proximity with each other. This conformational change is sufficient for the initiation of Epo-EpoR signal transduction. Here, we established a system of chemically regulated erythropoiesis in transgenic mice expressing a modified EpoR intracellular domain (amino acids 247-406) in which dimerization is induced using a specific compound (chemical inducer of dimerization, CID). Erythropoiesis is reversibly induced by oral administration of the CID to the transgenic mice. Because transgene expression is limited to hematopoietic cells by the Gata1 gene regulatory region, the effect of the CID is limited to erythropoiesis without adverse effects. Additionally, we show that the 160 amino acid sequence is the minimal essential domain of EpoR for intracellular signaling of chemically inducible erythropoiesis in vivo. We propose that the CID-dependent dimerization system combined with the EpoR intracellular domain and the Gata1 gene regulatory region generates a novel peroral strategy for the treatment of anemia.